Effect of planting media on growth of pineapple CV. Madu seedlings by stem cutting technique / Mohd Miqdam Jubidin, Mohammed Selamat Madom and Nur Aainaa Hasbullah - Jubidin, Mohd Miqdam; Madom, Mohammed Selamat; Hasbullah, Nur Aainaa (Universiti Teknologi MARA, Sabah, 2020)
Generally, pineapple sucker is used as the main planting material for commercial cultivation of pineapple. Pineapple sucker is usually obtained either from the stalk or the stem of a pineapple plant. Research to study the effect of planting media using mineral soil as the main component for the mixture on the growth of sucker by stem cutting technique was conducted. The objective of this research is to study the effects of mineral soil-based mixed planting media on the growth of pineapple suckers produced cultivated via stem cutting of Madu pineapple. The research was conducted at the Pineapple Nursery of the Faculty of Sustainable Agriculture, UMS Sandakan, from March 2019 until September 2019. The treatments used in this research were, soil as T1 (100%); Soil:coco peat as T2 (1:1,v/v); Soil:peat soil as T3 (1:1,v/v); Soil:sand as T4 (1:1,v/v). The data obtained showed there is a significant difference in the number of a successfully germinated sucker. However, no significant difference was detected for the sucker growth parameters. Planting media T3, soil: coco peat recorded the highest number of successfully germinated suckers (12.25). Meanwhile, for growing media, suggested T2 soil: peat soil were recorded the highest for root length (15.53 cm), leaf number (18.00), and stem diameter (2.18 cm) at 60 days after transplant (DAT).